Chordee and hooded prepuce with no hypospadias; outcome of urethral preservation surgery with spongioplasty - Mazen O. Kurdi (BMC Urology, 2025)
Abstract Background Deficient ventral prepuce is a rare anomaly of prepuce with normally situated meatus. It is usually associated with this or hypoplastic urethra. Methods A retrospective study included all infants diagnosed with a ventrally hooded prepuce. A penile degloving was the first step. Then reinforcement of the hypoplastic urethra by spongioplasty was performed. Sleeve resection of the hooded prepuce and reconstruction of sulcus corona was the last step. Results The mean operative time was 44 ± 9.5 min. A hypoplastic urethra was reported in 35 cases (30.4%). A urethral stent was inserted at the beginning of the procedure and removed at the end. Twelve patients (10.4%) developed urethral cutaneous fistulas by the end of the first postoperative month. Conclusion A hooded ventral prepuce with ventral chordee and normally situated meatus presents a challenge for paediatric surgeons. It is usually associated with a hypoplastic urethra. Attempts should be made to correct the chordee and preserve the urethra. The preserved urethra can be reinforced with spongioplasty. Unintended urethral injuries are common during dissection. Therefore, repairing the injury, reinforcing the dartos pedicle flap, and spongioplasty are suitable options. It is possible to preserve the urethra in patients having chordee without hypospadias. Utmost care should be taken to avoid urethral injuries which are common because shaft skin is stuck to the urethral skin. Urethral injuries can be repaired primarily; however, there is a high incidence of fistula.